Baby gorilla : photographic and descriptive atlas of skeleton, muscles and internal organs including CT scans and comparison with adult gorillas, humans and other primates /: photographic and descriptive atlas of skeleton, muscles and internal organs including CT scans and comparison with adult gorillas, humans and other primates. (2015) - Diogo, Rui; Pastor, Juan F; Hartstone-Rose, Adam; Muchlinski, Magdalena N
No abstract available